Can government-guided funds promote innovation output in strategic emerging enterprises? Evidence from China - Chunyan Zhao; Lu Zhang (PLoS ONE, 2025)
Using 9,138 observations from 731 strategic emerging enterprises in China’s A-share market between 2010 and 2023, this study explores the impact of government-guided funds on innovation in these enterprises and their underlying mechanisms. The main empirical findings are as follows: Firstly, there is a positive correlation between government-guided funds and innovation output in strategic emerging enterprises, and their endogeneity and robustness have been tested using instrumental variable methods and a series of other methods. Secondly, government-guided funds significantly enhance corporate innovation output through two pathways: one is by alleviating financing constraints on technological R&D; the other is by enhancing companies’ ability to access policy resources such as tax incentives. Thirdly, heterogeneity tests indicate that the innovative incentive effect of government-guided funds is more pronounced in eastern regions, state-owned enterprises, and companies with higher capital intensity from downstream customers. This study focuses on strategic emerging enterprises, providing a new perspective on the impact of government-guided funds on corporate innovation.